Impact of COVID-19 on the logistics management industry supply chain in Bangladesh: a case study on an MNC- Kuehne + Nagel - Ddahar, Ive (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.